Hepatitis B Vaccination Coverage and Its Associated Factors in Nurses of Imam Reza (AS) Hospital in Kermanshah - Edris Abdifard; Azadeh Faraji; Elham Sepahvand; Abbas Aghae; Alice Khachian (Journal of Client-centered Nursing Care, 2016)
Background: Viral hepatitis is one the main infections that health staff are faced with and nurses are at greater risk of the contracting this disease because of their exposure to patients. The current study was conducted to determine the hepatitis B vaccination coverage and its associated factors in nurses of Imam Reza (AS) Hospital in Kermanshah, Iran.